Jihadist terrorist attacks and far right party preferences: an ‘unexpected event during survey design’ in four European countries - Vlandas, T; Halikiopoulou, D (Cambridge University Press, 2024)
This article presents new empirical evidence about the impact of Jihadist terrorist attacks on far-right preferences using the “unexpected event during survey” research design. This strategy allows us to match individual-level data from the European Social Survey (ESS) to data on Jihadist terrorist attacks to compare respondents’ party preferences before and after a terrorist attack during the same survey period in the Netherlands, Sweden, France, and Germany. We theorise and test three distinct hypotheses about how different combinations of attitudinal changes including out-group prejudice and trust in institutions impact far-right preferences. We find no statistically significant effects. Analyses of the two indirect mechanisms— i.e., prejudice and trust—yield mixed results consistent with the null effect on far-right party preferences. By showing that terrorist attacks are unlikely to decisively change party support despite attracting significant public attention and affecting political attitudes, our results challenge the argument that Jihadist terrorism necessarily benefits the far-right and highlight the importance of null effects for overcoming confirmation bias in the study of voting behaviour.